2015
DOI: 10.1053/j.gastro.2015.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants That Predispose to DNA Double-Strand Breaks in Lymphocytes From a Subset of Patients With Familial Colorectal Carcinomas

Abstract: BACKROUND & AIMS DNA structural lesions are prevalent in sporadic colorectal cancer, so we proposed that gene variants that predispose to DNA double-strand breaks (DSBs) would be found in patients with familial colorectal carcinomas of an undefined genetic basis (UFCRC). METHODS We collected primary T cells from 25 patients with UFCRC and matched patients without colorectal cancer (controls) and assayed for DSBs. We performed exome sequence analyses of germline DNA from 20 patients with UFCRC and 5 undiagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Moreover, statistical inference indicates that the association is significant as the overall mutational burden of putatively pathogenic variants in our LLS patients was high whereas in the general population is low. Of note, several recently published studies have identified likely pathogenic variants in other genes that maintain DNA integrity, including NTHL1, FAN1, and MCM9 in cases with familial CRC with unknown genetic basis [25][26][27][28] and mutations in BLM in cases with earlyonset CRC [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, statistical inference indicates that the association is significant as the overall mutational burden of putatively pathogenic variants in our LLS patients was high whereas in the general population is low. Of note, several recently published studies have identified likely pathogenic variants in other genes that maintain DNA integrity, including NTHL1, FAN1, and MCM9 in cases with familial CRC with unknown genetic basis [25][26][27][28] and mutations in BLM in cases with earlyonset CRC [29].…”
Section: Discussionmentioning
confidence: 99%
“…Such an effect might explain the markedly greater activity of the drug combination in the longer-term clonogenic assays than the shorter cell viability assays. To address this possibility, we analyzed levels of γ-H2AX, a phosphorylated histone mark associated with unrepaired DNA breaks [27], in cells treated with vehicle, single drugs, or the pre:ada combinations for 72 h (Figure 4a and Figure S3a). This showed a significant increase in phospho-H2AX signal in cells treated with the drug combination versus single drugs, even at low overall drug concentrations.…”
Section: Combination Of Prexasertib and Adavosertib Enhances Dna Breamentioning
confidence: 99%
“…Families bearing the p.S478N variant in POLD1/p125 develop microsatellite stable, chromosomal unstable colorectal adenocarcinoma and/or oligopolyposis with high penetrance and dominant inheritance ( Palles et al, 2013 , Valle et al, 2014 ). We have described this variant in a patient with familial colorectal cancer, but not bearing mutations in canonical genes associated with risk ( Arora et al, 2015 ). A POLD1 p.L474P proofreading domain variant has also been identified in a patient with hereditary non-polyposis colorectal cancer and deemed pathogenic by evidence from co-segregation, in silico predictions of functionality and functional assay in yeast.…”
Section: Pold1 In Human Diseasementioning
confidence: 99%